Glucose availability is a decisive factor for Nrf2-mediated gene expression() - Heiss, Elke H. (Elsevier, 2013)
Activation of the transcription factor Nrf2 (nuclear factor-erythroid 2-related factor 2) is one of the major cellular defense lines against oxidative and xenobiotic stress, but also influences genes involved in lipid and glucose metabolism. It is unresolved whether the cytoprotective and metabolic responses mediated by Nrf2 are connected or separable events in non-malignant cells. In this study we show that activation of Nrf2, either by the small molecule sulforaphane or knockout of the Nrf2 inhibitor Keap1, leads to increased cellular glucose uptake and increased glucose addiction in fibroblasts. Upon Nrf2 activation glucose is preferentially metabolized through the pentose phosphate pathway with increased production of NADPH. Interference with the supply of glucose or the pentose phosphate pathway and NADPH generation not only hampers Nrf2-mediated detoxification of reactive oxygen species on the enzyme level but also Nrf2-initiated expression of antioxidant defense proteins, such as glutathione reductase and heme-oxygenase1. We conclude that the Nrf2-dependent protection against oxidative stress relies on an intact pentose phosphate pathway and that there is crosstalk between metabolism and detoxification already at the level of gene expression in mammalian cells.